2015
DOI: 10.1142/s0218625x1550047x
|View full text |Cite
|
Sign up to set email alerts
|

MICROSTRUCTURES, MICROHARDNESS, AND CRYSTALLIZATION BEHAVIORS OF AMORPHOUS Al2O3-YSZ COATINGS PREPARED BY AIR PLASMA SPRAYING

Abstract: Three types of amorphous Al 2 O 3 -yttria-stabilized zirconia (YSZ) coatings were prepared using air plasma spraying (APS). The e®ects of the APS parameters on the microstructure, porosity, amorphous-phase content, and microhardness of the coatings were investigated using scanning electron microscopy (SEM), di®erential scanning calorimetry (DSC), and transmission electron microscopy (TEM). The results indicated that the microstructure of the coatings was dependent on the APS parameters used. The porosity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This phenomenon was due to rapid cooling after the deposition process, and the atoms hardly diffuse to form an amorphous structure. Song et al [25] also obtained the Al 2 O 3 -40 vol.% 8YSZ as-sprayed coatings with different contents of the amorphous structure by changing the primary plasma gas during the APS process. It can be found that the coating was mostly built up by well-flattened splats, and there were also some regions with partly melted splats and splash debris.…”
Section: Phase and Microstructure Characterization Of Coatingmentioning
confidence: 99%
“…This phenomenon was due to rapid cooling after the deposition process, and the atoms hardly diffuse to form an amorphous structure. Song et al [25] also obtained the Al 2 O 3 -40 vol.% 8YSZ as-sprayed coatings with different contents of the amorphous structure by changing the primary plasma gas during the APS process. It can be found that the coating was mostly built up by well-flattened splats, and there were also some regions with partly melted splats and splash debris.…”
Section: Phase and Microstructure Characterization Of Coatingmentioning
confidence: 99%
“…Therefore, it is not enough to fabricate the amorphous ceramic coating only with high enthalpy and ultra‐fast cooling rate under the current technology. According to the results of reported studies, it was found that the ceramic coatings contained amorphous phase successfully prepared were belong to the multicomponent system like Al 2 O 3 ‐ZrO 2 , Al 2 O 3 ‐YSZ, and Al 2 O 3 ‐ZrO 2 ‐SiO 2 21–23,29,30 . Significantly, the ratio of multicomponent in sprayable powders was at the low eutectic point, the amorphous ceramic coatings were successfully prepared.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the stability of these amorphous alloys was poor under harsh service conditions, which changed the microstructure of the coating and further affected the performance of the coating.Recently, some manufactured amorphous ceramic coatings have been deposited. Noticeably, these amorphous ceramic coatings have high crystallization temperature [21][22][23][24], which make them have excellent microstructure stability in a wide temperature range for the application under harsh services conditions. In our previous work, the Al 2 O 3 -YAG amorphous ceramic coating was deposited via…”
mentioning
confidence: 99%
“…Recently, some manufactured amorphous ceramic coatings have been deposited. Noticeably, these amorphous ceramic coatings have high crystallization temperature [21][22][23][24], which make them have excellent microstructure stability in a wide temperature range for the application under harsh services conditions. In our previous work, the Al 2 O 3 -YAG amorphous ceramic coating was deposited via atmospheric plasma spraying (APS) used the Al 2 O 3 /YAG powders.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not enough to form the amorphous ceramic coating only with high enthalpy and ultra-fast cooling rate under the current technology. According to the results of reported studies, it is concluded that the ceramic coatings containing the amorphous phase successfully prepared were belong to the multicomponent [22][23][24][30][31][32]. Especially, the ratio of multi-component in sprayable powders was at low eutectic point, then the amorphous ceramic coating can be successfully prepared.…”
Section: Introductionmentioning
confidence: 99%